Image Of Considering Opinions Of The Fundamentalists In The Books Of Rhetoric - Moghalles, Marwan Mohammed Abdullah (Recep Tayyip Erdoğan Üniversitesi, 2022)
What is known is that most of the topics of the science of jurisprudence founded by Imam al-Shafi’i are related to the Arabic language, and that the sciences of the Arabic language in general and the science of semantics and rhetoric in particular are based on the induction of the language itself, but the induction of the fundamentalists is independent and different from the induction of other Arabic linguistic scholars. This is due to the different purpose, the goal of the fundamentalists is to extract rules that help in knowing the rulings contained in the texts. And since their induction was considered by linguistic scholars of the language - as the books of rhetoric were filled from the seventh century AH until our present time with their opinions in various ways - I tried to highlight some of the images of that consideration in this research, and it was represented by the transfer of their words and sometimes making them in exchange for the statements of the rhetoricians; And even preferring it at other times, as well as mentioning their terms, quoting from their books and referring to them, and the idea of research is an attempt to draw attention to the importance of the science of jurisprudence for specialists in Arabic language sciences.

Bilindiği üzere, imam Şafii’nin tesis ettiği Fıkıh usulü konularının ekseriyeti, Arap dili ile ilgilidir. Genelde Arap dili, özelde de meânî ve beyân ilimleri bizzat dilin kendi incelemeleri üzerine oluşturulmuştur. Ancak usul âlimlerinin onun hakkındaki incelemeleri dil âlimlerinin incelemelerinden farklı ve bağımsızdır. Bunun nedeni amaç ve gayenin farklı olmasıdır. Usul âlimlerinin amacı, nasların içerdiği hükümleri ortaya koymaya yardımcı olacak kural ve kaideler koymaya yöneliktir. Onların ortaya koydukları bu çalışmalar dil ilim insanları nazarında muteber olması nedeniyle belagat kitapları hicri yedinci yüzyıldan günümüze kadar onların farklı Biçimlerdeki görüşleri ile dolmuştur. Bu çalışmada, muteber bazı örnekleri ele almaya çalıştım. Çalışma, onların görüşlerinin aktarılması ve bazen onların görüşlerine karşıbeyân ehlinin görüşlerinin aktarılması,aksine bazen de bu görüşlerin tercih edilmesi şeklinde ortaya konulmuştur. Aynı zamanda kullandıkları terimler zikredilmiş, kitaplarından alıntılar yapılmış ve bunlara işaret edilmiştir. Bu çalışmanın ana fikri, Arap dili uzmanlarının dikkatlerini, fıkıh usulü ilminin önem ve ehemmiyetine çekebilmek amacına yöneliktir.

إنَّ مما هو معلوم أن أكثر مباحث علم أصول الفقه الذي أسّسه الإمام الشافعي متعلقة باللغة العربية، وأنَّ علوم اللغة العربية عموما وعلمي المعاني والبيان خصوصا قائمةٌ على أساس استقراء اللغة ذاتها، إلَّا أنَّ استقراء الأصوليين لها مستقلٌّ ومختلفٌ عن استقراء غيرهم من علماء اللغة؛ وذلك لاختلاف الغاية، فهدف الأصوليين هو استخلاص قواعد تُعِينُ على معرفة الأحكام التي تتضمَّنها النصوص، ولمَّا كان استقراؤهم معتبرًا عند أهل اللغة -حيثُ امتلأت كتب البلاغة منذ القرن السابع الهجري حتى عصرنا الحالي بآرائهم بصور شتى- حاولتُ إبراز بعض من صور ذلك الاعتبار في هذا البحث، وقد تمثلتْ بنقل أقوالهم وجعلها في بعض الأحيان في مقابل أقوال البيانيين؛ بل وترجيحها في أحيان أخرى، وكذا ذكر مصطلحاتهم، والاقتباس من كتبهم والإحالة إليها، وفكرة البحث محاولة للفت الأنظار إلى أهمية علم أصول الفقه للمتخصِّصين في علوم اللغة العربية.
Keywords: Arabic; Jurisprudence; Fundamentalists; Rhetoric books; The relationship between jurisprudence and rhetoric: Arap Dili; Fıkıh Usûlü; Usûl Âlimleri; belagat kitapları; Belâgat-Usûl İlişkisi; Din Araştırmaları; اللغة العربية; أصول الفقه; علماء الأصول; كتب البلاغة; العلاقة بين البلاغة والأصول; Religious Studies